Governance: Who controls matters - Bruno Deffains; Dominique M. Demougin (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
In this paper, we provide an outlook for further research on the topic of governance. We review four different approaches on the theory of the firm and discuss implications for governance, namely; nexus of contracts / agency theory, property rights / incomplete contracts, adaption, and nexus of specific investments.
Keywords: 330; Corporate Governance; Agency Theory; Theorie der Unternehmung; Theorie